2022
DOI: 10.1111/nhs.12919
|View full text |Cite
|
Sign up to set email alerts
|

Post accidental injury: Mediating roles of emotional expressivity, rumination, and posttraumatic growth

Abstract: This study explored the relationship between rumination (deliberate or intrusive), emotional expressivity (positive or negative), and posttraumatic growth among patients within 1 month after an accidental injury. Using a cross-sectional design, 313 patients were investigated in two comprehensive hospitals. The results revealed that intrusive rumination had a significant positive effect on posttraumatic growth, partly through four different pathways: (i) the mediating role of deliberate rumination; (ii) the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…With the emphasis on harmonious and balanced relationships in Chinese culture, it is common for Chinese individuals to follow cultural expectations to conceal negative emotions in social interactions, even when facing traumatic events (Wei et al, 2013 ). In line with this, a previous study found that negative emotional expressivity was not associated with positive well-being among Chinese victims of accidental injuries (Pan et al, 2022 ). During the COVID-19 pandemic, a qualitative study also showed that Chinese healthcare workers experienced difficulties in expressing negative emotions with close others, to avoid disrupting social harmony (Hsu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 72%
“…With the emphasis on harmonious and balanced relationships in Chinese culture, it is common for Chinese individuals to follow cultural expectations to conceal negative emotions in social interactions, even when facing traumatic events (Wei et al, 2013 ). In line with this, a previous study found that negative emotional expressivity was not associated with positive well-being among Chinese victims of accidental injuries (Pan et al, 2022 ). During the COVID-19 pandemic, a qualitative study also showed that Chinese healthcare workers experienced difficulties in expressing negative emotions with close others, to avoid disrupting social harmony (Hsu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 72%
“…With Chinese culture's emphasis on interpersonal harmony that encourages concealing negative emotions in social interactions (Leung, 1998), it is not common for Chinese individuals to express distress even when facing traumatic events (Wei et al, 2013). Positive emotional expressivity (but not negative emotional expressivity) was found to be more associated with AG among Chinese victims of accidental injuries (Pan et al, 2022). Moreover, a qualitative study during COVID-19 showed that Chinese healthcare workers experienced difficulties with expressing negative emotions with close others to avoid disrupting social harmony (Hsu et al, 2020).…”
Section: Coping Strategies In Association With Agmentioning
confidence: 96%
“…Most previous research has focused on the relationship between rumination (both deliberate and intrusive) and post-traumatic growth. The results have shown that deliberate rumination is more conducive to post-traumatic growth ( 29 ). Therefore, we are inclined to encourage deliberate rumination after the experience of traumatic events, so as to enhance our understanding of such events and gain useful experience.…”
Section: Introductionmentioning
confidence: 99%